Program Pelatihan Peningkatan Kemampuan Public Speaking dan Presentation Skills bagi Mahasiswa Disabilitas di Perguruan Tinggi - Damri Damri; Gaby Arnez; Jumiati Jumiati; Nenny Mahyuddin; Mardhatillah Zulpiani; Yosa Yulia Nasri; Setia Budi; Rara Ajeng Pratiwi; Fauziah Salsabila Azhar; Gisela Virlinia (INTEGRITAS : Jurnal Pengabdian, 2026)
Students with disabilities in higher education face serious challenges in public communication skills, which impact academic participation and workplace readiness. Limited access to inclusive public speaking training exacerbates these barriers. This article aims to describe the implementation and impact of an adaptively designed public speaking and presentation skills training program for students with disabilities at Padang State University. This study involving 20 students with various disabilities. Data were collected through observation, in-depth interviews, documentation, and pretest and posttest instruments. Data were then analyzed using triangulation and the Wilcoxon test. The results showed a significant improvement in participants' presentation skills after the training, with significant contributions in building confidence, structuring message content, and using more effective expressions. These findings contribute to inclusive education practices by providing a training model that can be replicated at other universities. The conclusions emphasize the importance of experiential training programs and assistive technology in empowering students with disabilities and recommend the development of sustainable training with a multimodal approach.